Marketing Message Planning (Promotion) Qurban Animal Fund Raising Program Baitul Muttaqin Keputih Mosque Surabaya Period 2016 - Rizka Susanti Masulah (Airlangga Development Journal, 2021)
In 2016 Baitul Muttaqin mosque is able to get 21 cows and 30 goats. From the preliminary study with thecommittee, it was found that the results were obtained by establishing a special committee that moves to plan upto carry out marketing services of qurban animal fund receipts.As for the method of research, authors usequalitative research case study with data source interviews to 3 people involved in the special committee ofexcavation of qurban animal fund Baitul Muttaqin Keputih mosque Surabaya. The findings of the authors, withthe results of interviews 3 speakers, Qurban animal fund raising committee Baitul Muttaqin Keputih mosqueSurabaya perform steps - steps in accordance with the theoretical basis that the author uses to plan marketingmessages.